Zastosowanie metody podobieństwa do rejonizacji ekonomiczno- przemysłowej - Knychała, Krystyna (Wydział Prawa i Administracji UAM, 1972)
The article presents the possible application of taxonomic method of similarity for the division of Poland's districts into regions according to their industrialisation level. Application of similarity methods involves several conditions connected with the choice of diagonal features. The first part of the article was devoted to a theoretical description of those cnoditions. Next a division of Poland's districts was accomplished with help of Spearman's coefficient of rank correlation on the basis of selected and examined diagonal features. The basis of establishing the industrialized regions was a statement of the value of the coefficients of all the district combinations in, the table and in the diagram of similarities. They were plotted on a cartogram and next several conclusions concerning localization of industries in Poland were submitted. In the third part of the article the correctness of the accomplished division was veryfied by means of three measures: the arithmetic mean, the coefficient of variation and the t-est. In the conclusion some remarks on the disadvantages and advantages of the similarity method presented in the article were made.
Aplication of Similarity Method for Division in Industrial Regions